Combined influence of TAS2R38 genotype and PROP phenotype on the intensity of basic tastes, astringency and pungency in the Italian taste project. (January 2022) - Robino, Antonietta; Concas, Maria Pina; Spinelli, Sara; Pierguidi, Lapo; Tepper, Beverly J.; Gasparini, Paolo; Prescott, John; Monteleone, Erminio; Gallina Toschi, Tullia; Torri, Luisa; Pagliarini, Ella; Gasperi, Flavia; et al.
Highlights: TAS2R38 genotype differently associates with intensity ratings of PROP and tastants. Response to PROP is higher in PAV/PAV and PAV/AVI than in AVI/AVI individuals. Response to tastants is higher in AVI/AVI than in PAV/AVI and PAV/PAV individuals. TAS2R38 is the primary determinant of intensity of tastes and astringency. Gender is the primary determinant of intensity of pungency followed by PROP status. Abstract: The combined influence of TAS2R38 genotype and PROP phenotype on oral sensations is still to be clarified. The present work investigates their influence on the intensity of basic tastes and somatosensory stimuli (capsaicin, aluminium sulphate), using a large cohort of 1117 individuals. The possible influences of gustin genotype and fungiform papillae density were also assessed. PROP phenotype was mainly associated with TAS2R38 genotype with AVI/AVI individuals reporting the lowest mean bitterness intensity (12.6 ± 1.26), and PAV/AVI individuals rating PROP lower (46.53 ± 0.93) than PAV/PAV individuals (54.14 ± 1.33). However, 25% of AVI/AVI subjects reported PROP bitterness perception higher than 'moderate' and small percentages of both PAV/PAV and PAV/AVI responded very little to PROP stimulation. PROP phenotype significantly affected ratings to all the tastant solutions with ST subjects giving the highest ratings and NT the lowest. An unexpected systematic effect of TAS2R38 diplotype on perceived intensity was found, with AVI/AVI individuals rating tastant solution intensity higher than PAV/AVI and PAV/PAV for all the stimuli. Recursive partitioning analysis was used to determine the influence of the explanatory variables (TAS2R38 diplotype, PROP status, age and gender) on intensity for each tastant solution. Regression trees indicated that TAS2R38 genotype is the most important variable for explaining differences in intensity of basic tastes and astringency, when compared to PROP responsiveness, gender, and age. Gender was the primary determinant of heightened perception of pungency. PROP status was the second most influential variable in all the models, with limited influence only on sweetness and umami perception. No significant variations of intensity of taste and somatosensory sensations were found in association to gustin polymorphism or fungiform papillae density. These findings call for a re-examination of the notion that the TAS2R38 gene uniquely controls PROP tasting and for future research devoted to a more in-depth genetic characterization of the AVI/AVI group and its possible associations with other polymorphisms.